An Overview of Molecularly Imprinted Polymers Embedded with Quantum Dots and Their Implementation as an Alternative Approach for Extraction and Detection of Crocin. Issue 21 (1st June 2022) - ul Gani Mir, Tahir; Malik, Azad Qayoom; Singh, Jaskaran; Shukla, Saurabh; Kumar, Deepak
Abstract: Molecularly imprinting polymer (MIPs) is an emerging technology that could provide an alternative path to produce receptor‐like binding sites. The technology involves complex bond formation between target molecules (templates), and functional monomers can occur insolvent. MIPS embedded with Quantum Dots (QDs) as a sensor is used for extraction and detection of various compounds. QDs have fluorescence properties and electronic characteristics such as comprehensive and continuous absorption spectra, narrow emission spectra, and high light resistance. Crocin is the major metabolite obtained from saffron ( Crocus sativus ). It is widely used as an antioxidant, antidiabetic, antitumor, and anticancer agent. According to recent studies, crocin has been used for drug delivery to treat various diseases. Therefore, the isolation, extraction and detection of crocin from saffron are of prime importance. Developing a selective extraction and detection technique for crocin would assist in its separation and purification easily from saffron stigmas. MIPs encapsulated with QDs is a promising tool for the extraction and detection of various compound, and this technique could also be employed for crocin. In this review, a brief summary of MIPs, QDs and MIP‐QDs sensors has been summarised. Moreover, an effort has been made to review how MIPs encapsulated with QDs can be used as the best alternative for efficiently extracting and detecting crocin. Abstract : MIPs embedded with QDs has a unique property of Extraction and detection. QDs have fluorescence properties and electronic characteristics such as comprehensive and continuous absorption spectra, narrow emission spectra, and high light resistance. Since there is a little literature available on extraction of crocin using MIPs therefore, understanding the possibilities by which MIPs embedded with QDs for extraction and detection of crocin is essential to understand. MIPs embedded with QDs can be employed as an alternative method for extraction and detection of crocin efficiently.